Ellenbogenluxationen im Kindesalter - Frongia, Giovanni; Günther, Patrick; Romero, Philipp; Kessler, Markus; Holland-Cunz, Stefan (Der Unfallchirurg, 2012)
Traumatic dislocation of the elbow is rare in children with an incidence of 3-6% of all elbow injuries. In the literature the outcome after elbow dislocation in childhood is rarely discussed. In the present study 33 children treated in our clinic from 2001 to 2008 with an acute traumatic dislocation of the elbow were retrospectively included. All events were unilateral whereby 1 child (3%) showed a recurrence of elbow dislocation after 9 weeks, 30% had a pure dislocation, 70% had a concomitant fracture, 55% showed a fracture of the medial epicondyle, 6% a fracture of the lateral epicondyle and 9% a further fracture. Of the fractures 83% required open reduction with osteosynthesis. After an average of 4.5 years 20 children (61%) were clinically examined. There were no instabilities of the joint and only minor clinical limitations of the range of motion. The established Mayo elbow performance score showed good to excellent results for all children. Despite severe joint trauma with frequently accompanying fractures, post-traumatic functional deficits are rarely limiting, independent of the accompanying fracture. The frequency of recurrence is low and instabilities were not seen.